2019
DOI: 10.1111/jgh.14615
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir‐based direct acting antiviral therapies for patients with hepatitis C virus genotype 2 infection

Abstract: Background and Aim Data regarding the comparative effectiveness and safety of sofosbuvir (SOF) in combination with ribavirin (RBV), daclatasvir (DCV), or ledipasvir (LDV) for hepatitis C virus genotype 2 (HCV‐2) patients were limited. We aimed to evaluate the performance of these regimens in Taiwan. Methods One hundred eighty‐seven HCV‐2 patients with compensated liver diseases receiving SOF in combination with RBV (n = 82), DCV (n = 66), or LDV (n = 39) for 12 weeks were retrospectively enrolled. The effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 43 publications
5
18
1
Order By: Relevance
“…However, when LDV is combined with SOF, which serves as a backbone with a potent antiviral activity and a high genetic barrier against all HCV genotypes, 21 the integrated analysis showed that 12‐week LDV/SOF was associated with high SVR12 rates (overall 98%) in patients with genotype 2 HCV, irrespective of fibrosis stage or treatment history. The results are consistent with a recently published Taiwan real‐world study in genotype 2 patients, which reported an SVR12 of 100% with LDV/SOF ( n = 39), compared with 94% with SOF + RBV ( n = 82) and 99% with SOF plus daclatasvir ( n = 66) 22 . Similarly, a real‐world study in genotype 2 Japanese patients ( n = 58) reported an SVR12 of 95% with 12‐week LDV/SOF, with high efficacy in most subgroups including older age, compensated cirrhosis, and treatment experience 23 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, when LDV is combined with SOF, which serves as a backbone with a potent antiviral activity and a high genetic barrier against all HCV genotypes, 21 the integrated analysis showed that 12‐week LDV/SOF was associated with high SVR12 rates (overall 98%) in patients with genotype 2 HCV, irrespective of fibrosis stage or treatment history. The results are consistent with a recently published Taiwan real‐world study in genotype 2 patients, which reported an SVR12 of 100% with LDV/SOF ( n = 39), compared with 94% with SOF + RBV ( n = 82) and 99% with SOF plus daclatasvir ( n = 66) 22 . Similarly, a real‐world study in genotype 2 Japanese patients ( n = 58) reported an SVR12 of 95% with 12‐week LDV/SOF, with high efficacy in most subgroups including older age, compensated cirrhosis, and treatment experience 23 .…”
Section: Discussionsupporting
confidence: 92%
“…The results are consistent with a recently published Taiwan real-world study in genotype 2 patients, which reported an SVR12 of 100% with LDV/SOF (n=39), compared with 94% with SOF+RBV (n=82) and 99% with SOF plus daclatasvir (n=66). 22 Similarly, a real-world study in genotype 2 Japanese patients (n=58) reported an SVR12 of 95% with 12-week LDV/SOF, with high efficacy in most subgroups including older age, compensated cirrhosis, and treatment experience. 23 A propensity score matched analysis undertaken in the same study showed no statistically significant difference (P=0.57) in SVR12 rates between LDV/SOF (96%) and glecaprevir/pibrentasvir (98%).…”
Section: Discussionmentioning
confidence: 95%
“…Three (16.7%) patients were non-SVR after being treated with this regimen (Table 5, case numbers 6–8), two of the non-SVR patients had active HCC, and all of the non-SVR patients had clinically significant portal hypertension defined by either platelet count < 100 (10 9 /L) and splenomegaly or LSM> 20kPa [23, 27]. Real-world data from Taiwan have shown high SVR rates with this regimen in genotype 2 patients with advanced fibrosis (98.5% and 100%, respectively) [28, 29]. Therefore, the higher non-SVR rate with this regimen in our study was due to advanced cirrhosis and active HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although SOF-based DAAs have been widely used for the treatment of HCV infection, there exist concerns regarding the safety of these regimens for patients with severe renal impairment because the serum concentration of inactive metabolite GS-331007 is highly elevated in these patients. 29,30 In contrast, the NS3 protease inhibitors, NS5A inhibitors, and the NS5B non-nucleotide polymerase inhibitors are mainly metabolized by the liver, and therefore, no dosage adjustment is needed for patients with renal impairment. Our study showed that the SVR 12 rate of PrOD for 12 weeks was excellent (100%) for East Asian HCV GT1b non-cirrhotic patients receiving hemodialysis and was comparable with the response rates in clinical trials and real-world studies.…”
Section: Discussionmentioning
confidence: 99%